Um percurso teórico-metodológico para leitura de “O isqueiro mágico” e “A rainha da neve”, de Hans Christian Andersen (1805-1875) - Jurazeky, Rosana da Silva Santos [UNESP] (2014)
The survey A methodological theoretical pathway for reading “The tinderbox” and “The snow queen” by Hans Christian Andersen (1805-1875), based on the concept of language understood as a process of human interaction and the act of reading, as a complex activity, involving not only grammatical and semantic aspects, but pragmatic and dialogic ones. This theoretical concept was adopted since it agrees with the goals of this investigation: 1) to analyze the textual and thematic structure of two H. C. Andersen’s tales, “The tinderbox” and “The snow queen”, selected from the corpus of his work, noticing similarities regarding the theme, subject, message; plot; time, space and place; the narrator and narrative focus and the characters; 2) to define criteria for the choice of a book or a short story from children's literature; 3) suggest activities that may contribute to the instruction of children’s literature in classrooms. The focus of the study was defined in relation to the narrative/classic text of children's literature. The activities developed undertaken were of bibliographic nature and accompanied the entire process of investigation. Finally, the fact of reading is one of the major problems experienced by school and by society as a whole, such as those relating to functional illiteracy, non-formation of the reader and lack of understanding of literary texts, justifies a research that will contribute to overcoming the problems experienced by school, when it comes to reading.